Artificial Intelligence in Islamic Communication: An Ethical Concern - Muhammad Atiq Ullah; Haque, Md. Shahidul; Md. Meerajul Islam (Journal of Islamic Communication and Counseling, 2026)
This study examines the ethical implications of Artificial Intelligence (AI) in Islamic communication through a qualitative systematic review. Twenty-one peer-reviewed articles published between 2020 and 2025 were selected through Google Scholar and manual screening. The review analyzes publication trends, research methodologies, and dominant thematic areas within existing literature. The findings indicate that most studies employ conceptual or qualitative approaches, with major themes encompassing AI and Islamic ethics, AI in Islamic education, AI-mediated religious communication, and AI governance frameworks. Several studies emphasize the risk of misinterpretation in AI-generated Qur’anic and Hadith content. Additional ethical concerns include deepfakes, surveillance practices, and algorithmic bias in recommendation systems. Conversely, the literature highlights opportunities for enhanced access to religious knowledge and innovative educational applications. Overall, this review demonstrates that while the current body of research offers valuable ethical insights, it remains predominantly conceptual, underscoring the need for comparative studies and empirical investigations into the application of AI in Islamic communication.